The flavonoid quercetin ameliorates Alzheimer's disease pathology and protects cognitive and emotional function in aged triple transgenic Alzheimer´s disease model mice (2015)
ABSTRACT: Alzheimer’s disease (AD) is the most common senile dementia in the world. Although important progress has been made in understanding the pathogenesis of AD, current therapeutic approaches provide only modest symptomatic relief. In this study, we evaluated the neuroprotective effect of quercetin (25 mg/kg) administration via i.p. injection every 48 hours for 3 months on aged (21–24 months old) triple transgenic AD model (3xTg-AD) mice. Our data show that quercetin decreases extracellular β-amyloidosis, tauopathy, astrogliosis and microgliosis in the hippocampus and the amygdala. These results were supported by a significant reduction in the paired helical filament (PHF), β-amyloid (βA) 1–40 and βA 1–42 levels and a decrease in BACE1-mediated cleavage of on learning and spatial elevated plus maze test. Together, these findings suggest that quercetin reverses histological hallmarks of AD and protects cognitive and emotional function in aged 3xTg-AD mice.